MEMBANGUN CITRA KAMPUS MELALUI KEPUASAN MAHASISWA BERDASARKAN KUALITAS LAYANAN - ', Setiyawan (Fakultas Ekonomi Universitas Wisnuwardhana, 2016)
Abstract: Various attempts were made to build University image andone of them is to provide a great quality service for students, so cancreate a trustful campus image through student satisfaction. Qualityservices such as direct evidence, reliability, responsiveness, assurance,and empathy that given to students are a powerful benefits for easinessand convenience obtained service. Meanwhile, campus image suchas corporate image, user image, and product image with mediatingvariables satisfaction regarding product expectation and value. Thisresearch shows that direct effect of service quality in campus imageIt means that provided quality service standard can exceed customerexpectations so it can increase campus image, and student satisfactionvariable can not be used as intervening variable. It means that studentsatisfaction variable has not been able to strengthen (moderating)relationship between service quality and campus image.Key words: Quality services, Campus image and Satisfaction.